Evaluation of nutrition potential in different cultivars of elephant grass - Sales, Francisco Sérgio M.; Viana, Obed Jeronimo; Albuquerquer, José Jackson L. de (Pesquisa Agropecuaria Brasileira, 2014)
A comparative trial with different cultivars of elephant grass (Pennisetum purpureum Schum.) was carried out to determine their forage quality. The experimental design was completely randomized and factorial 2 x 19 (two cutting times and 19 cultivars) with two replications. The results, considering the mean data of two cutting times, sugest: a. As for crude protein content in dry matter: IRI-534 (7.53%), Urukwona (7.34%), Cameron (7.28%), IRI-381 (6.69%) and Taiwan-145 (6.64%) were the best in comparison with others. b. As for digestibility in vitro: Taiwan-145 (40.65%), IRI-381 (39.98%), Kisoze (38.86%), IRI-185 (38.85%), IRI-323 (38.62%), Malaia-2247 (37.13%), IRI-328 (35.15%), IRI-534 (34.15%), Napier (34.13%), Mineiro (33.78%), IRI-382 (32.95%), Merker (32.58%) and Urukwona (31.93%) showed a trend to better performance in comparison with others. c. Higher digestive dry matter yield (in tons/ha) was obtained with Taiwan-145 (2.71), Malaia-2247 (2.45), IRI-381 (2.42), Urukwona (2.41), Mineiro (2.27), IRI-323 (2.26), IRI-328 (2.20), Kisoze (2.18), IRI-185 (2.13) and IRI-329 (1.74). d. Having in mind the final evaluation criteria, cultivars with best nutritive potential were: Taiwan-145, Malaia-2247, IRI-381, Urukwona, Mineiro, and IRI-323.